Effect of staggered vs. simultaneous co-administration of bempedoic acid on pharmacokinetics of pravastatin: Randomized, Cross-Over Clinical Trial in Healthy Volunteers - Stoll, Felicitas E.; Amato, Salvatore; Sauter, Max; Burhenne, Jürgen; Weiß, Johanna; Haefeli, Walter E.; Blank, Antje (Pharmaceutics, 2025)
Background/Objectives: Bempedoic acid (BA) is a novel cholesterol-lowering agent with proven positive effects on cardiovascular endpoints. Because it is an inhibitor of the hepatic transporters OATP1B1 and OATP1B3, two uptake transporters regulating the intrahepatic availability of statins, it increases the systemic exposure of co-administered statins. This interaction could raise the risk of myopathy. We hypothesized that the drug interaction between BA and statins could be mitigated by staggered administration. Methods: This was a single-centre, open-label, randomized, two-arm, cross-over, phase I drug interaction trial in healthy volunteers (EudraCT-No: 2022-001096-13). The primary objective was to evaluate the OATP1B1 inhibitory effect of BA on exposure to pravastatin after simultaneous administration versus different schedules of staggered administration. A secondary objective was to evaluate the impact of SLCO1B1 genotypes (*1, *5, *15, *37) on pravastatin exposure. Pravastatin was administered in single oral doses of 40 mg at six visits. After a baseline visit with pravastatin alone, BA was dosed to steady state at the approved oral dose of 180 mg. Outcome measures were the area under the plasma concentration-time curve, extrapolated to infinity (AUC∞) and Cmax of pravastatin, 3α-hydroxy-pravastatin (pravastatin 3-iso), and pravastatin lactone, and their geometric mean ratios (GMRs) of different schedules of administration. Log-transformed AUC∞ and Cmax were compared with one-way ANOVA with a 90% confidence interval (CI). Results: Fourteen participants completed all visits. At BA steady state, the GMRs of pravastatin AUC∞ and Cmax were 1.80 (90% CI 1.31-2.46) and 1.95 (90% CI 1.40-2.72), respectively, compared to baseline. There was no significant difference in pravastatin exposure between simultaneous vs. staggered administration. There was no statistically significant difference in pravastatin 3-iso or pravastatin lactone between different administration modes. For the AUC∞ of pravastatin and pravastatin 3-iso, haplotype was a significant source of variation (63% and 20%, respectively), while the type of administration (simultaneous vs. staggered) had no significant impact. Conclusions: The increase in pravastatin exposure with concomitant intake of BA was larger than expected. There was no significant difference between simultaneous vs. staggered administration of pravastatin and BA, possibly due to a population that was heterogenous in SLCO1B1 haplotypes.